INVESTIGATING NURSES STRATEGIES FOR REDUCING MEDICATION ERRORS. - Amrah Maqabool Almaqadi, Wafa Joher Alanber, Mohammed Obaid M Rubaian, Abdullmajed Mohammed Almaiteeq, Ohoud Suliman Alotibi, Marayif Hamoud Aldawsari, Abrah Swilem Mubrook Almubrook, Wafa Saad Alharthi, Yahya Yahya Akkam, ,; Fahad Mohammed Aldawsari, Rahmah Mohammed Alhawsawi, Mohammed Faleh Al Muteri, Mutab Marshoob Alkareeni, Mohmmad Ahmed Mohmmad Alzhrani, Maha Matar Thawab Almutairi, Naif Mukammi Alanazi, (Chelonian Research Foundation, 2022)
There are serious dangers to patient safety in the healthcare system from medication errors. These mistakes, which can happen at different points during the prescription process, are frequently the consequence of miscommunication, system malfunctions, or human error. The frequency, causes, and effects of pharmaceutical errors are examined in this abstract, along with preventative measures and initiatives. Adoption of technologies that have demonstrated promise in lowering error rates, such as electronic prescriber order entry, automated drug distribution, and barcode medicine delivery, are important areas of focus. Another important aspect of mistake identification and prevention that is emphasized is the role that clinical pharmacists play in medication management. Further initiatives to improve pharmaceutical safety include addressing staffing difficulties, strengthening communication between healthcare practitioners, and putting in place double-check procedures. Raising awareness and supporting best practices in medication administration is greatly aided by healthcare professionals' education and training programs. Medication errors persist despite continuous efforts, making research, alertness, and cooperation among healthcare stakeholders necessary to further decrease their frequency and improve patient safety. Key words: Medication errors, patient safety, healthcare, technology, clinical pharmacists, communication, human error, medication administration, healthcare professionals, intervention strategies.